The Correlation Between Parity And Mother's Employment With Exclusive Breast Feeding To Infants In Sidomulyo And Roworejo Villages, Working Area Of UPT Puskesmas Roworejo - Anggi Kusuma; Eva Yunitasari; Putri Yunita Sari (Universitas Haji Sumatera Utara, 2023)
Only 44% of infants worldwide are nursed during the first hour of birth, according to data from the World Health Organization (WHO), and only a few babies younger than 6 months are still exclusively breastfed. A pre-survey at the Roworejo Public Health Center revealed that in 2020, 37,96% of babies aged 0 to 6 months were exclusively breastfed. In 2021, 39,74% of babies were breastfed exclusively.The research objective was to determine the correlation between parity and mother's occupation with exclusive breastfeeding to babies in Sidomulyo and Roworejo Villages in the working area of Roworejo Public Health Center 2022. The type of research design was analytic observational with a cross-sectional approach. The samples taken were 81 mothers with an accidental sampling technique. The measuring instrument used was a checklist sheet and bivariate analysis using the Chi-Square. The results showed that p-value = 1,000 there was no correlation between maternal parity and exclusive breastfeeding in Sidomulyo and Roworejo Villages. Then, there was a correlation between the mother's occupation and exclusive breastfeeding in Sidomulyo and Roworejo Villages in the working area of Roworejo Public Health Centre 2022 with a p-value = 0,013. The results of this research are expected for the Roworejo Public Health Centre to provide health education to working mothers about exclusive breastfeeding.